A Step Forward in the Minimization of Political Corruption in Financial Support of Political Parties: The Experience of Ukraine and Lithuania - Kulish Anatoliy; Andriichenko Nadiia; Reznik Oleg (Baltic Journal of Law & Politics, 2018)
Political corruption as a negative phenomenon hampers the democratic and economic development of any state. The experience of foreign countries across the world testifies to the existence of number of reasons conducive to the spread of political corruption. Its study is important both for Ukraine, which is actively taking measures to combat political corruption, and for other countries with a high level of political corruption.